Organic-inorganic lithium ion battery composite diaphragm and preparation method thereof

By combining inorganic nanoparticles with traditional separators, a composite separator with uniform surface and excellent mechanical strength was prepared, which solved the problem of lithium-ion battery separator being undustable under high temperature conditions and improved the safety and performance of the battery.

CN119542673APending Publication Date: 2025-02-28ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484401.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators are not durable under high temperature conditions and are prone to melting, resulting in battery short circuits and explosions.

Method used

Inorganic nanoparticles are combined with traditional separators, and a composite separator with uniform surface and excellent mechanical strength is prepared through specific slurry formulation and coating processes.

Benefits of technology

It improves the high temperature resistance and mechanical properties of the diaphragm, reduces the risk of battery short circuit and explosion, and enhances battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542673A_ABST
    Figure CN119542673A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy automobile battery diaphragms, in particular to an organic-inorganic lithium ion battery composite diaphragm and a preparation method thereof.The preparation method comprises the following steps that 1, deionized water and 1 / 3 of a binder are added into a slurry mixing machine at a time according to the mass ratio of nanoparticles to a dispersing agent to a thickening agent to the binder to a wetting agent being 1: 0.005: 0.015: 0.06: 0.005, after stirring and dissolving are conducted, stirring is conducted for 1-2 h, and a slurry is obtained; continuously adding a thickening agent, stirring until the thickening agent is completely dissolved, then adding Al2O3 nanoparticles, sanding, adding a wetting agent, stirring, standing, defoaming, sieving and discharging to obtain slurry for later use; and 2, preparing the composite diaphragm by adopting the slurry obtained in the step 1 through a blade coating method of a lithium ion battery diaphragm coating machine. The preparation method is simple and convenient to operate, and the prepared lithium ion battery composite diaphragm has the characteristics of uniform surface and excellent mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery diaphragms for new energy vehicles, and in particular to an organic-inorganic lithium-ion battery composite diaphragm and a preparation method thereof. Background Art

[0002] Due to its high energy density, long cycle life, stable charge and discharge rate, excellent charge retention and capacity recovery capabilities, power lithium-ion batteries have great applications in new energy vehicles, new energy buses, intelligent robots, smart balance cars, smart phones, smart bracelets, portable imaging devices, etc. The development of new lithium-ion batteries and their materials has also attracted widespread attention from more and more researchers and industry personnel.

[0003] Lithium-ion batteries contain four major elements: positive electrode, negative electrode, electrolyte and diaphragm. As one of the key components of lithium-ion batteries, the diaphragm isolates the positive and negative electrodes in lithium-ion batteries to prevent battery short circuits. It also acts as a channel for lithium ion transmission, allowing ions to move freely during charging and discharging. Commercial lithium-ion battery diaphragm materials are mainly polyethylene, polypropylene, polyvinylidene fluoride, etc. Traditional diaphragm base films are not resistant to high temperatures under high temperature conditions due to low porosity and intrinsic defects of high molecular polymers. When the diaphragm melting point is reached or exceeded, it is easy to cause the diaphragm to melt, resulting in a short circuit between the positive and negative electrodes of the battery, and even causing serious accidents such as battery explosions and vehicle fires. Therefore, in recent years, a composite coated diaphragm that combines inorganic nanoparticles with traditional diaphragms has been developed at home and abroad to enhance the high temperature resistance of battery diaphragms and improve the safety performance of battery cells.

[0004] Alumina is an inorganic substance, a white powder, with the chemical formula of Al2O3, which has the characteristics of high purity, good dispersion, high specific surface area, high temperature resistance, significant inertness, good stability, etc. It is used for plasticization and heat resistance of various ceramics and refractory materials, and is widely used in aerospace, food packaging, cosmetic filling, coating printing and dyeing, etc. However, there are few studies in the prior art to obtain a method for preparing a lithium-ion battery composite diaphragm with uniform diaphragm surface and excellent mechanical strength. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide an organic-inorganic lithium-ion battery composite diaphragm and a preparation method thereof, so that the obtained lithium-ion battery composite diaphragm has a uniform surface, excellent mechanical strength, and is simple and convenient to operate.

[0006] Based on the above purpose, the present invention provides a method for preparing an organic-inorganic lithium-ion battery composite diaphragm, comprising the following steps:

[0007] Step 1: according to the mass ratio of nanoparticles: dispersant: thickener: binder: wetting agent = 1: 0.005: 0.015: 0.06: 0.005, add deionized water and 1 / 3 of the binder in a slurry mixer at one time, stir and dissolve, continue to add the thickener and stir until it is completely dissolved, then add the nanoparticles, add the wetting agent after sand grinding, stir, stand for degassing, sieve, and discharge to obtain a slurry for use;

[0008] Step 2: Use the slurry obtained in step 1 to prepare a composite diaphragm by a lithium-ion battery diaphragm coater blade coating method.

[0009] In step 1, the binder and thickener are one of sodium carboxymethyl cellulose, sodium alginate, hydroxyethyl cellulose and acrylate.

[0010] In step 1, the speed of the slurry mixer is 1200-2400RPM, and the stirring time is 10-360min. Preferably, the speed of the slurry mixer is 2000RPM, and the stirring time is 30min.

[0011] In step 1, the nanoparticles are one of silicon oxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, iron oxide, and titanium oxide.

[0012] The number of cycles of the sanding in step 1 is 2-30 times, and the rotation speed is 550-650RPM. Preferably, the number of cycles of the sanding is 16 times.

[0013] The wetting agent in step 1 is one of laureth-9, sulfonated oil, pull-opening powder BX, soybean lecithin, thiols, hydrazides and thiol acetals.

[0014] The degassing time in step 1 is 5-60 minutes, and the mesh size of the sieve is 400 meshes. Preferably, the degassing time is 15 minutes.

[0015] Step 2: The method for preparing a composite diaphragm by a lithium-ion battery diaphragm coater scraping method comprises the following steps: firstly, mixing the slurry, placing a coating roller, installing a scraper, and starting the coater; adjusting the unwinding tension and the winding tension, as well as the oven temperature, and online monitoring the diaphragm thickness and surface density at the diaphragm winding point.

[0016] The unwinding tension is 4.0-10.0N, the winding tension is 2.5-6.0N; the temperature of the oven is 50-70°C.

[0017] The present invention also provides an organic-inorganic lithium-ion battery composite membrane, which is obtained by the preparation method. The particle size of the lithium-ion battery composite membrane slurry is measured by a Malvern laser particle size analyzer to determine the dispersion effect and ensure the uniformity and consistency of the composite membrane.

[0018] Beneficial effects of the present invention:

[0019] (1) The present invention combines inorganic nanoparticles with organic diaphragms to prepare organic-inorganic lithium-ion battery composite diaphragms, which has great advantages in the application of new energy fields and has the characteristics of simple method and easy operation.

[0020] (2) The present invention uses the unique micro-nano pores of inorganic nanoparticles to provide a unique space for the uniformity of the diaphragm. The prepared composite diaphragm has the characteristics of regular morphology, controllable thickness and uniform surface density.

[0021] (3) The present invention uses inorganic nanoparticles to coat the surface of the base film, which improves the tensile properties and thermal shrinkage characteristics of the diaphragm, has good mechanical properties, and is more cost-effective. The organic-inorganic lithium-ion battery diaphragm prepared by the present invention has broad application prospects in the field of new energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 1 and 2 are SEM images of the organic-inorganic lithium-ion battery composite separators of Examples 1, 2 and 3 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0025] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.

[0026] Example 1

[0027] The method for preparing the organic-inorganic lithium-ion battery composite diaphragm of this embodiment comprises the following steps:

[0028] (1) According to the mass ratio, Al2O3: dispersant: CMC: binder: wetting agent = 1: 0.005: 0.015: 0.06: 0.005, add deionized water and 1 / 3 of the binder (acrylate) into the slurry mixer at one time, start stirring, and stir at a speed of 1200RPM for 30 minutes until it is completely dissolved; continue to add thickener (sodium carboxymethyl cellulose), stir at the same speed for 1 hour, open the cylinder every 30 minutes during high-speed stirring to check the dissolution, if there are undissolved micelles, scrape the cylinder, and continue stirring until it is completely dissolved; then, add nanoparticles into the slurry mixing cylinder, connect the sand mill, and sand grind. The sand grinding cycle is 10 times, and the sand mill speed is 600RPM; finally, turn off the sand mill, add the wetting agent (laureth-9) into the slurry mixing cylinder according to the proportion, stir at a low speed of 500RPM for 45 minutes, let it stand for degassing for 5 minutes, sieve, discharge, and set aside.

[0029] (2) The composite diaphragm was prepared by the blade coating method of a lithium-ion battery diaphragm coater. The slurry was stirred at a rate of 300 RPM in a stirring tank to mix the slurry evenly. The air valve was connected, the coating roller was placed, the scraper was installed, and the coater was turned on. The unwinding tension (7.0±3.0N) and the winding tension (2.5-6.0N) as well as the oven temperature (55-70°C) were adjusted, and the diaphragm thickness and surface density were monitored online at the diaphragm winding point.

[0030] The test results are shown in Table 1 below: The total thickness of the organic-inorganic lithium-ion battery composite diaphragm prepared in this embodiment is 14.38 μm, and the surface density is 11.43 g / m 2 , puncture strength 5.84N, air permeability 255.10s / 100mL, peel strength 132N / m, moisture content 623.60. The scanning electron microscope image of the composite diaphragm prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the prepared lithium-ion battery composite membrane has regular morphology, controllable thickness and uniform surface density.

[0031] Example 2

[0032] The method for preparing the organic-inorganic lithium-ion battery composite diaphragm of this embodiment comprises the following steps:

[0033] (1) According to the mass ratio, Al2O3: dispersant: CMC: binder: wetting agent = 1: 0.005: 0.015: 0.06: 0.005), deionized water and 1 / 3 of the binder (sodium carboxymethyl cellulose) were added into the slurry mixer at one time, stirring was started, and high-speed stirring was performed at a speed of 1500 RPM for 60 min until it was completely dissolved; the thickener (sodium carboxymethyl cellulose) was continued to be added, and stirring was performed at the same speed for 2 h. During the high-speed stirring process, the dissolution was checked every 30 minutes. If there were undissolved micelles, the slurry was scraped and stirring was continued until it was completely dissolved; then, the nanoparticles were added into the slurry mixer, and the slurry mixer was connected to the sand mill for sand grinding. The sand mill was cycled 16 times at a speed of 600 RPM. Finally, the sand mill was turned off, and a wetting agent (laureth-9) was added to the mixing cylinder in proportion. The mixture was stirred at a low speed of 500 RPM for 45 min, allowed to stand for degassing for 30 min, sieved, discharged, and set aside.

[0034] (2) The composite diaphragm was prepared by the scraping method of the lithium ion battery diaphragm coater. The slurry was stirred at a rate of 100 RPM in a stirring tank to mix the slurry evenly. The air valve was connected, the coating roller was placed, the scraper was installed, and the coater was turned on. The unwinding tension (7.0 N) and the winding tension (6.0 N), as well as the oven temperature (60 ° C) were adjusted, and the diaphragm thickness and surface density were monitored online at the diaphragm winding point.

[0035] The test results show that the total thickness of the organic-inorganic lithium-ion battery composite membrane prepared in this embodiment is 13.66 μm, and the surface density is 10.48 g / m 2 , puncture strength 5.68N, air permeability 249s / 100mL, peel strength 104N / m, moisture content 558.50. The scanning electron microscope image of the composite diaphragm prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the prepared lithium-ion battery composite membrane has regular morphology, controllable thickness and uniform surface density.

[0036] Example 3

[0037] The method for preparing the organic-inorganic lithium-ion battery composite diaphragm of this embodiment comprises the following steps:

[0038] (1) According to the mass ratio of Al2O3: dispersant: CMC: binder: wetting agent = 1:0.005:0.015:0.06:0.005, deionized water and 1 / 3 of the binder (sodium carboxymethyl cellulose) were added into the slurry mixer at one time, stirring was started, and high-speed stirring was performed at a speed of 1600 RPM for 30 min until it was completely dissolved; the thickener (sodium carboxymethyl cellulose) was continued to be added, and stirring was performed at the same speed for 2 h. During the high-speed stirring process, the dissolution was checked every 30 min. If there were undissolved micelles, the slurry was scraped and stirring was continued until it was completely dissolved; then, the nanoparticles were added into the slurry mixer, and the slurry was connected to the sand mill for sand grinding. The sand mill was cycled 20 times at a speed of 600 RPM. Finally, the sand mill was turned off, and a wetting agent (laureth-9) was added to the mixing cylinder in proportion. The mixture was stirred at a low speed of 500 RPM for 45 minutes, allowed to stand for degassing for 10 minutes, sieved, discharged, and set aside.

[0039] (2) The composite diaphragm was prepared by the scraping method of a lithium-ion battery diaphragm coater. The slurry was stirred at a rate of 150 RPM in a stirring tank to mix the slurry evenly. The air valve was connected, the coating roller was placed, the scraper was installed, and the coater was turned on. The unwinding tension (7.5 N) and the winding tension (5.5 N), as well as the oven temperature (65 ° C) were adjusted, and the diaphragm thickness and surface density were monitored online at the diaphragm winding point.

[0040] The test results show that the total thickness of the organic-inorganic lithium-ion battery composite membrane prepared in this embodiment is 13.96 μm, and the surface density is 10.43 g / m 2 , puncture strength 6.74N, air permeability 268.10s / 100mL, peel strength 114N / m, moisture content 525.60. The scanning electron microscope image of the composite diaphragm prepared in this example is as follows Figure 1 As shown in the figure, it can be seen that the prepared lithium-ion battery composite membrane has regular morphology, controllable thickness and uniform surface density.

[0041] Table 1 Physical and chemical properties of organic-inorganic lithium-ion battery composite membranes for implementation cases 1, 2, and 3

[0042]

[0043] The invention has the advantages of simple operation, obvious effect, uniform surface and excellent mechanical strength, and has high research value and application prospect.

[0044] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an organic-inorganic lithium-ion battery composite diaphragm, characterized in that: The steps include: Step 1: according to the mass ratio of nanoparticles: dispersant: thickener: binder: wetting agent = 1: 0.005: 0.015: 0.06: 0.005, add deionized water and 1 / 3 of the binder in a slurry mixer at one time, stir and dissolve, continue to add the thickener and stir until it is completely dissolved, then add the nanoparticles, add the wetting agent after sand grinding, stir, stand for degassing, sieve, and discharge to obtain a slurry for use; Step 2: Use the slurry obtained in step 1 to prepare a composite diaphragm by a lithium-ion battery diaphragm coater blade coating method.

2. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step 1, the binder and thickener are one of sodium carboxymethyl cellulose, sodium alginate, hydroxyethyl cellulose and acrylate.

3. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step 1, the speed of the slurry mixer is 1200-2400RPM, and the stirring time is 10-360min.

4. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: In step 1, the nanoparticles are one of silicon oxide, aluminum oxide, potassium oxide, sodium oxide, calcium oxide, magnesium oxide, iron oxide, and titanium oxide.

5. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: The number of cycles of the sanding in step 1 is 2-30 times, and the rotation speed is 550-650RPM.

6. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: The wetting agent in step 1 is one of laureth-9, sulfonated oil, pull-opening powder BX, soybean lecithin, thiols, hydrazides and thiol acetals.

7. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: The degassing time in step 1 is 5-60 minutes, and the mesh size of the sieve is 400 meshes.

8. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 1, characterized in that: Step 2: The method for preparing a composite diaphragm by a lithium-ion battery diaphragm coater scraping method comprises the following steps: firstly, mixing the slurry, placing a coating roller, installing a scraper, and starting the coater; adjusting the unwinding tension and the winding tension, as well as the oven temperature, and online monitoring the diaphragm thickness and surface density at the diaphragm winding point.

9. The method for preparing the organic-inorganic lithium-ion battery composite diaphragm according to claim 8, characterized in that: The unwinding tension is 4.0-10.0N, the winding tension is 2.5-6.0N; the temperature of the oven is 50-70°C.

10. An organic-inorganic lithium-ion battery composite diaphragm, characterized in that: The method is adopted to obtain the product according to any one of claims 1 to 9.